Functional hepatic recovery after xenotransplantation of cryopreserved fetal liver cells or soluble cell-factor administration in a cirrhotic rat model: Are viable cells necessary? - Ochenashko, O; Nikitchenko, Yu; Volkova, N; Mazur, S; Somov, A; Fuller, B; Petrenko, А (Journal of Gastroenterology and Hepatology, 2008)
Background and Aim: Chronic liver failure results in the decrease of the number of functioning hepatocytes. It dictates the necessity of using exogenous viable cells or/and agents that can stimulate hepatic regenerative processes. Fetal liver contains both hepatic and hematopoietic stem cells with high proliferative potential, which may replace damaged cells. Also, immature cells produce fetal-specific factors which may support the injured liver. Our aim was to test the ability of human fetal liver cells and cell-free fetal-specific factors of non-hepatic origin to stimulate recovery processes in an experimental model of carbon tetrachloride–induced cirrhosis in rats. Methods: Cirrhotic rats were intrasplenically injected with fetal liver cells (1 × 107 cells/0.3 mL medium) or cell-free fetal-specific factors (0.3 mL/1 mg protein). Control groups received medium alone. Serum indexes, hepatic functions, and morphology were evaluated for 15 days. Result: Human fetal liver cell transplantation was shown to abrogate the mortality of cirrhotic animals, to improve serum markers, and to restore liver mitochondrial function and detoxification. Morphological patterns of liver recovery were observed by histology. In comparison, an injection of fetal-specific factors produced similar functional recovery, whilst a more limited liver regeneration was observed by histology. Conclusions: The positive effects of fetal liver cell and cell-free fetal-specific factors in experimental cirrhosis may result from the presence of stage-specific factors activating hepatocellular repair.
Keywords: cell transplantation; cirrhosis; cryopreservation; fetal-specific factors; human fetal liver cell; human fetal liver cell; liver progenitor cells